(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2016)
This investigation was carried out to evaluate the nutritional and microbiological quality of germinated soy flour. Protein content of germinated soy flour was 6.90% higher than the non-germinated soy flour. Essential amino acids content, including Lysine, Valine and Threonine was increased by 8.53%, 8.50% and 7.93% respectively. In addition, vitamin B2 and iron contents were also increased by 14.29% & 8.80% respectively, compared to non-germinated soy flour. Germination resulted in nutritionally enriched soy flour as compared to non-germinationated one. The microbiological quality parameters including total bacterial count, total coliform count, fecal indicator Escherichia coli and yeast & mold count was found to be within acceptable level throughout the 6 months of storage at ambient temperature. No food borne pathogen including Salmonella spp. Staphylococcus aureus was detected. Furthermore, spore forming bacteria including Bacillus cereus was not detected in any of the germinated soy flour sample tested. In addition, fungal metabolites including aflatoxins B1, B2, G1 and G2 could not be detected in any sample. Nutritional and microbiological finding of this study, indicate the germinated soy flour could be used as raw material or ingredient for making diverse food and bakery products. Bangladesh J. Sci. Ind. Res. 51(3), 167-174, 2016